Antibacterial activity of bangle rhizome essential oil (zingiber montanum) against streptococcus mutans - Devina RS. Pardosi; Cicih B. Purnamasari; Swandari Paramita; Lilies A. Astuti; Masyhudi; Enos T. Arung (Journal of Dentomaxillofacial Science, 2022)
Objective: This research was conducted to determine the potential of bangle rhizome essential oil (zingiber montanum) as an antibacterial against the growth of streptococcus mutans. Material and Methods: Tests are carried out using the diffusion method for the well’s technique. In this study, eugenol was used as a positive control. Essential oil was diluted with acetone and obtained essential oil of bangle rhizome with a concentration of 3.12%, 6.25%, 12.5%, 25%, and 50%. Results: That bangle rhizome essential oil succeeded in inhibiting the growth of streptococcus mutans with the minimum inhibitory concentration 3.12% and with the optimal inhibitory concentration 50%. Conclusion: It is concluded from this research that essential oil from bangle rhizome is a strong, new natural antibacterial agent for streptococcus mutans. There was a slight difference of antibacterial effectiveness between eugenol, as positive control, and essential oil from bangle rhizome on streptococcus mutans bacterial growth observed from their inhibition zones.